2020
DOI: 10.1111/1742-6723.13631
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Pre‐hospital provider clinical judgement upon arrival to the emergency department: A systematic review and meta‐analysis

Abstract: Pre-hospital providers (PHPs) undertake initial patient assessment, often spending considerable time with patients prior to arrival at ED. However, continuity of this assessment with ongoing care of patients in the ED is limited, with repeated assessment in the ED, starting with the process of triage in hospital. A systematic review of the literature was conducted to assess the ability of PHPs to predict patient outcomes in the ED. Manuscripts were screened and were eligible for inclusion if they included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…It is expected that further training and familiarisation of paramedics with patient flow through EDs may improve concordance levels. Concordance with streaming decision in this study was higher than that reported by a recent systematic review which looked at pre‐hospital providers' ability to predict disposition (admission vs discharge), triage score category, clinical requirements, or mortality prior to discharge 9 . These results raise the prospect that paramedic‐guided streaming may improve overall patient flow in the ED.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…It is expected that further training and familiarisation of paramedics with patient flow through EDs may improve concordance levels. Concordance with streaming decision in this study was higher than that reported by a recent systematic review which looked at pre‐hospital providers' ability to predict disposition (admission vs discharge), triage score category, clinical requirements, or mortality prior to discharge 9 . These results raise the prospect that paramedic‐guided streaming may improve overall patient flow in the ED.…”
Section: Discussioncontrasting
confidence: 78%
“…Paramedics can stream patients with high accuracy when compared to the current model of using streaming nurses. This was despite paramedics having limited knowledge of patient load within the ED and therefore inherently biasing the results towards 9 These results raise the prospect that paramedic-guided streaming may improve overall patient flow in the ED. There is scope for paramedics' clinical acumen and knowledge of the patient to be utilised to expedite the triage process.…”
Section: Discussionmentioning
confidence: 94%
“…Strict adherence to National Early Warning Score (NEWS) by general practitioners was shown to have the potential to increase (unneeded) hospital admissions 15. Classification of disease severity based on developed decision rules is inferior compared with clinical performance 16–20…”
Section: Introductionmentioning
confidence: 99%
“…Many prediction models suffer from methodological limitations, such as low sample sizes and poor internal and/or external validation. [6][7][8][9] Despite published guidelines and published reporting standards, 10,11 the majority of prediction model studies do not follow methodological recommendations and therefore have a high risk of bias. This bias limits their validity, which in turn could jeopardize patient care and also results in research waste.…”
mentioning
confidence: 99%